The Role of Storytelling in Effective Public Speaking (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article explores the pivotal role of storytelling in enhancing the effectiveness of public speaking. Storytelling is a timeless and powerful communication tool that can captivate audiences, convey complex ideas, and foster lasting connections. Drawing from the fields of psychology, rhetoric, and communication, this study delves into the science and art of storytelling, examining its psychological impact, structure, and strategies. By understanding the profound influence of storytelling, speakers can elevate their public speaking skills, engage their audiences, and leave a lasting impact.